Sensing the schoolyard - Maria João Silva (2010)
This paper presents the Usense2learn platform, a platform designed and implemented to enable children and teachers to use georeferenced multisensory information together with information acquired by sensors. Usense2learn places the creation of content in the hands of children. While using Usense2learn, mobile sensors can be held across the exploration area and provide georeferenced environmental information such as air temperature and humidity. Using multimedia (video, image, sound and text) teachers and children can bring the outside world into their classroom and share it with other classrooms across the globe. Having the limited schools' budgets in mind, content creation can be made anywhere without communication costs. Internet connection is only required, together with Google Earth, for visualization. The Usense2learn platform was successfully used in a curricular context, engaging children and teachers in meaningful environmental education activities. Â© 2010 ACM.